Logics of violence: Religion and the practice of philosophy - Beardsworth, Richard (Cultural values, 2000)
By considering the way in which the mechanism of the scapegoat in René Girard's work is predicated on a phenomenal and anthropic understanding of violence, the following shows how Girard's anthropological conception of religion determines and limits from the beginning relations between the violent and the nonviolent and the phenomenal and the nonphenornenal. This conception is then inscribed within a larger economy of violence that opens up Girard's account of victimization and sacrifice to wider determinations. Important distinctions are made along the way between the human sciences, religion, ethics and philosophy. If the work of Jacques Derrida in particular and deconstruction in general permit this widening in this article, I then argue however that such concepts as originary violence also short‐circuit the differentiations, with which we are concerned, to address, with and beyond Girard, a radical ethics of the lesser violence.